EMS Non-Transport of Low-Risk COVID-19 Patients. (3rd April 2023) - Couturier, Katherine; Nelson, Alexander R.; Burns, Kevin; Cone, David C.; Rollins, Mark; Venkatesh, Arjun K.; Ulrich, Andrew; Shapiro, Matthew; Joseph, Daniel
Abstract: Objectives: COVID-19 infections in the community have the potential to overwhelm both prehospital and in-hospital resources. Transport of well-appearing patients, in the absence of available emergency department treatment capacity, increases strain on the hospital and EMS system. In May of 2020, the Connecticut Office of EMS issued a voluntary, EMS-initiated, non-transport protocol for selected low-risk patients with symptoms consistent with COVID-19. We evaluated the implementation of this non-transport protocol in a mixed urban/suburban EMS system. Methods: We conducted a retrospective review of contemporaneously recorded quality improvement documentation for uses of the Connecticut COVID-19 non-transport protocol by EMS clinicians within our EMS system during two implementations: from 12/14/2020 to 5/1/21, and again from 1/3/22 to 2/18/22, which coincided with large COVID-19 case surges in our region. Results: The vast majority of patients treated under the non-transport protocol were not reevaluated by EMS or in our emergency departments in the subsequent 24 hours. There was reasonable adherence to the protocol, with 83% of cases appropriate for the non-transport protocol. The most common reasons for protocol violations were age outside of protocol scope (pediatric patients), failure of documentation, or vital signs outside of the established protocol parameters. We did not find an increased 24-hour ED visit rate in patients who were inappropriately triaged to the protocol. Of patients who had ED visits within 24 hours, only two were admitted, none to higher levels of care. Conclusion: Within this small study, EMS clinicians in our system were able to safely and accurately apply a non-transport protocol for patients presenting with symptoms consistent with COVID-19. This is consistent with previous literature suggesting that EMS-initiated non-transport is a viable strategy to reduce the burden on health systems.